Retrieval of the P wave reflectivity response from autocorrelation of seismic noise: Jakarta Basin, Indonesia. Issue 2 (27th January 2017) - Saygin, Erdinc; Cummins, Phil R.; Lumley, David
Abstract: We autocorrelate the continuously recorded seismic wavefield across a dense network of seismometers to map the P  wave reflectivity response of the Jakarta Basin, Indonesia. The proximity of this mega city to known active faults and the subduction of the Australian plate, especially when the predominance of masonry construction and thick sedimentary basin fill are considered, suggests that it is a hot spot for seismic risk. In order to understand the type of ground motion that earthquakes might cause in the basin, it is essential to obtain reliable information on its seismic velocity structure. The body wave reflections are sensitive to the sharp velocity contrasts, which makes them useful in seismic imaging. Results show autocorrelograms at different seismic stations with reflected‐wave travel time variations, which reflect the variation in basement depth across the thick sedimentary basin. We also confirm the validity of the observed autocorrelation waveforms by conducting a 2‐D full waveform modeling. Key Points: Seismic risk is high in Jakarta, and the subsurface basin structure is still poorly understood The basin response of Jakarta is mapped from stacked autocorrelations of the continuous seismic noise recorded across a seismic array The relative change of arrival times of autocorrelograms suggests a thinning of the basin from the north to the south